History of coeducation and its dissemination in the western formal education - Gordillo, Enrique (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
In the context of the current public debate about the superiority single-sex schooling versus coeducation, critics of the latter often argue that coeducation spread in western formal education not specifically because of research-proven benefits, but rather due to ideological sociological reasons. The following study presents a historical route along some of the milestones that led to coeducation in the Western system as we know it (with a final emphasis on the Peruvian process). It concludes that the expansion of coeducation was not due to scientifically-proven benefits but to sociological or economic pressures. The paper concludes that the debate mentioned above can legitimately take up its sustenance in that demonstrated lack of empirical evidence.